Whole transcriptome data of primary human NK cells under hypoxia and interleukin 15 priming: A 2×2 factorial design experiment - Figueiredo, Ana Sofia; Killian, Doreen; Schulte, Jutta; Sticht, Carsten; Lindner, Holger A. (Data in Brief, 2017)
Natural Killer (NK) cells mediate innate immunity against cancer and intracellular infection, at that, operating in often oxygen-deprived environments. We performed a microarray experiment with a 2×2 factorial design to profile gene expression in human NK cells (Velasquez et al., 2016) [1]. In this experiment, NK cells from 5 healthy volunteers were primed or not for 6 h with the survival factor and inflammatory cytokine interleukin 15 (IL-15) under hypoxic or normoxic culture conditions (20 samples in total). Here, we provide details on the culture setup that govern the actual O2 partial pressure (pO2) experienced by the cells, as well as on the RNA extraction procedure used, which we optimized from commercial spin column protocols to obtain highly concentrated total RNA. We present a quality control analysis of the normalized microarray data, as well as overviews for differentially regulated genes. These data provide insights into NK cell transcriptional responses to immune stimulation under physiologically relevant low oxygen conditions. This dataset is deposited in the Gene Expression Omnibus database (accession number GSE70214).